The Role of Glycemic Control in Inflammation Markers and Clinical Outcomes in Type 2 Diabetes Patients with Severe COVID-19 - Lavinia Craciun; Flavia Ignuta; Uma Shailendri Rayudu; Maliha Afra; Ovidiu Rosca; Adrian Vlad; Oana Aburel; Dana Emilia Velimirovici (Biomedicines)
Background and Objectives: Patients with type 2 diabetes mellitus (T2DM) are at a heightened risk of adverse outcomes from Coronavirus Disease 2019 (COVID-19). However, the influence of glycemic control on systemic inflammation and clinical severity remains incompletely understood. This study aimed to compare inflammatory markers, composite severity scores, and clinical outcomes between T2DM patients with COVID-19 who had well-controlled diabetes (hemoglobin A1c < 7%) versus those with poorly controlled diabetes (hemoglobin A1c ≥ 7%). Methods: We retrospectively reviewed 181 adult patients with T2DM and severe COVID-19 admitted to a tertiary hospital between January 2022 and December 2023. Patients were divided into two groups: well-controlled (n = 117) and poorly controlled (n = 64) T2DM. Baseline demographics, comorbidities, and laboratory parameters (C-reactive protein, interleukin-6, ferritin, neutrophil and lymphocyte counts, platelets, and calculated indices such as the neutrophil-to-lymphocyte ratio [NLR] and systemic immune-inflammation index [SII]) were collected. Composite severity scores (APACHE II, CURB-65, and NEWS) and clinical outcomes (ICU admission, mechanical ventilation, mortality, and length of stay) were compared. Statistical tests used included Student’s t-test or the Mann–Whitney U for continuous variables and chi-square for categorical variables, with p < 0.05 deemed significant. Results: The two groups did not differ significantly in age or duration of diabetes (p = 0.40 and p = 0.75, respectively). Patients with poorly controlled T2DM exhibited higher inflammatory markers (mean CRP of 93.4 mg/L vs. 78.6 mg/L, p = 0.002; IL-6 of 64.2 pg/mL vs. 52.8 pg/mL, p = 0.004) and elevated severity scores (APACHE II of 16.8 vs. 14.1, p = 0.001). Poor glycemic control was associated with higher ICU admissions (39.1% vs. 22.2%, p = 0.02) and mortality (14.1% vs. 6.0%, p = 0.05). Conclusions: In T2DM patients hospitalized with COVID-19, poor glycemic control correlates with heightened inflammatory responses, worse composite severity scores, and increased rates of unfavorable outcomes. These findings underscore the necessity of stringent glucose management to mitigate inflammation and improve prognoses in this vulnerable patient population.